Efficacy of targeted therapies after PD-1/PD-L1 blockade in metastatic renal cell carcinoma. Issue 17 (November 2015) - Albiges, Laurence; Fay, André P.; Xie, Wanling; Krajewski, Katherine; McDermott, David F.; Heng, Daniel Y.C.; Dariane, Charles; DeVelasco, Guillermo; Lester, Renee; Escudier, Bernard; Choueiri, Toni K.
Highlights: The efficacy of targeted therapy (TT) after PD-1/ PD-L1 blockade is unknown in mRCC. We conducted a retrospective analysis of mRCC patients treated with PD-1/PD-L1 blockade and subsequent TT. Median time to treatment failure on subsequent TT was 6.6 months. 1-year and 2-year OS from the initiation of subsequent TT was 58% and 36%. Both VEGF/VEGFR and mTOR inhibitors demonstrated activity following PD-1/PD-L1 blockade. Abstract: Background: Monoclonal antibodies that target the programmed death-1 (PD-1)/programmed death-ligand 1(PD-L1) pathway have shown antitumour activity in metastatic renal cell carcinoma (mRCC) and are currently being developed in first-line (in combination) and in previously treated patients. The efficacy targeted therapy (TT) after PD-1/PD-L1 blockade is still unknown. Methods: Medical records of mRCC patients treated with investigational PD-1 or PD-L1 inhibitors at 4 academic institutions were reviewed. Patients who received subsequent treatment with TT were selected to collect outcome measures of subsequent TT. Results: Of 99 patients who received PD-1/PD-L1 blockade as part of clinical trials, 56 patients have received subsequent therapy: 44 patients received vascular endothelial growth factor (VEGF)/vascular endothelial growth factor receptor (VEGFR) inhibitors and 12 received mammalian target of rapamycin (mTOR) inhibitors as first subsequent TT. Median follow up, from the start of subsequent TT was 16.1 months (range: 0.2, 30.6 months). TT post PD-1/PD-L1 blockade was administered as second-line, third-line or beyond third-line in 9 (16%), 24 (43%) and 23 patients (41%) respectively. Median time to treatment failure on subsequent TT was 6.6 months (range: 0.2+, 23.0). 1-year and 2 year overall survival from the initiation of subsequent TT was 58% (95% confidence interval (CI): 41–72%) and 36% (95% CI: 18–54%), respectively. Conclusion: Both VEGF/VEGFR and mTOR inhibitors demonstrate antitumour activity following PD-1/PD-L1 blockade.